Contemporary reappraisal of the efficacy of adjuvant chemotherapy in resected retroperitoneal sarcoma: Evidence from a nationwide clinical oncology database and review of the literature. (June 2017) - Datta, Jashodeep; Ecker, Brett L.; Neuwirth, Madalyn G.; Geha, Rula C.; Fraker, Douglas L.; Roses, Robert E.; Karakousis, Giorgos C.
Abstract: Background: While margin-negative resection remains the cornerstone of therapy for retroperitoneal sarcoma (RPS), the impact of adjuvant chemotherapy (AC) on overall survival (OS) remains poorly understood. Methods: The National Cancer Data Base was queried for patients undergoing curative-intent resection of primary non-metastatic RPS (2004–2013). Multivariable modeling identified factors associated with AC receipt. Cox regression identified covariates associated with OS, and AC and surgery alone (SA) cohorts were matched 1:1 by propensity scores based on these covariates. In the propensity-score matched cohort, OS was compared by Kaplan-Meier estimates. Results from this analysis were presented in the context of a review of the existing literature on the impact of AC in resected RPS. Results: Of 3892 resected RPS patients, 90.0% and 10.0% received SA and AC, respectively. Predictors of AC receipt included younger age, non-Caucasian race, hospital location, histologic grade, adjacent organ invasion, and histologic subtype. The propensity score-matched cohort comprised 767 patients (SA n = 377; AC n = 390); at a median follow-up of 59.2 (IQR 35.0–85.3) months, median OS of the propensity-matched cohort was 53.6 (IQR 22.4–119.5) months. Utilization of AC was associated with significantly worse long-term survival (median OS: 47.8 vs. 68.9 months, p = 0.017; HR 1.30, 95% CI 1.05–1.61). AC was not associated with improved OS in margin-positive (R1/R2) resection, high-grade (G2/G3) and larger (>10 cm) tumors, or in any histologic subtype. Albeit not statistically significant, there was a trend toward improved OS with AC in spindle cell (HR 0.37, 95% CI 0.10–1.38), giant cell (HR 0.82, 95% CI 0.32–2.13), and synovial (HR 0.26, 95% CI 0.05–1.33) sarcoma. Conclusions: Data from a large nationwide oncology database and review of the existing literature do not support adjuvant chemotherapy regimens following curative-intent resection of RPS, even in subgroups at high risk of failure (e.g., R1/R2 resection, high-grade or large tumors). The possible benefit of conventional adjuvant regimens in spindle cell, giant cell, and synovial sarcoma should be explored in prospective studies. Highlights: Analysis of a contemporary cohort of US patients with resected retroperitoneal sarcoma (RPS) revealed that a majority (90%) of patients are treated with surgical resection alone. Predictors of adjuvant chemotherapy receipt included younger age, non-Caucasian race, hospital location, histologic grade, adjacent organ invasion, and histologic subtype. Utilization of adjuvant chemotherapy was associated with significantly worse long-term survival compared with resection alone; adjuvant chemotherapy was not associated with improved overall survival in margin-positive (R1/R2) resection, high-grade (G2/G3) and larger (>10 cm) tumors, or in any histologic subtype. Albeit not statistically significant, there was a trend toward improved overall survival with adjuvant chemotherapy in spindle cell, giant cell, and synovial sarcoma, a finding that warrants prospective exploration.